Analisa Evaluasi Dana Bantuan Sosial (Bansos) di Kecamatan Medan Area Kota Medan Provinsi Sumatera Utara - Putri, Sarah Adelia (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of the Evaluation Analysis Of Social Assistance Funds (Bansos) in the Medan District, Madya City Area, North Sumatra Province. This study will focus on the formulation of the problem, namely How the Standard Operating Procedure (SOP) in the distribution of social assistance as an effort to reduce poverty in the Medan Area District and what are the inhibiting factors in the implementation of the distribution of Social Aid Funds and what are the criteria for the process and supervision of Social Aid Funds. The results showed that the positive impact of the policy of providing social assistance to the poor was to provide assistance in the form of basic necessities or money in order to ease the burden on the poor. While the negative impacts such as educating lazy life, prone to conflict, and educating consumptive life. As for the factors that influence the policy of providing social assistance such as budget or funds, coordination with certain fields, and community activities.